2013
DOI: 10.1177/2045125312472890
|View full text |Cite
|
Sign up to set email alerts
|

A review of the suitability of duloxetine and venlafaxine for use in patients with depression in primary care with a focus on cardiovascular safety, suicide and mortality due to antidepressant overdose

Abstract: Depression and anxiety disorders are among the most common disorders treated by general practitioners (GPs) in the UK. Since both disorders are associated with a significantly increased risk of suicide, including with antidepressant overdose, the safety of antidepressants in overdose is of paramount importance. Numerous updates relating to antidepressant safety have been issued by regulators in the UK which may have eroded GP confidence in antidepressants. Venlafaxine, a serotonin nor adrenaline reuptake inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…Anticonvulsants for fibromyalgia syndrome (Üceyler 2017 b);Monoamine oxidase inhibitors (MAOIs) for fibromyalgia syndrome (Tort 2012);Non-steroidal anti-inflammatory drugs (NSAIDs) for fibromyalgia (Derry 2017);Analgesics and opioid agents for fibromyalgia syndrome;Sedatives and hypnotic agents for fibromyalgia syndrome;Selective serotonin reuptake inhibitors (SNRIs) for fibromyalgia syndrome (Walitt 2015);Serotonin and noradrenaline reuptake inhibitors (SNRIs) for fibromyalgia syndrome (Häuser 2013 a)Tricyclic agents for fibromyalgia syndrome. …”
Section: Notesmentioning
confidence: 99%
“…Anticonvulsants for fibromyalgia syndrome (Üceyler 2017 b);Monoamine oxidase inhibitors (MAOIs) for fibromyalgia syndrome (Tort 2012);Non-steroidal anti-inflammatory drugs (NSAIDs) for fibromyalgia (Derry 2017);Analgesics and opioid agents for fibromyalgia syndrome;Sedatives and hypnotic agents for fibromyalgia syndrome;Selective serotonin reuptake inhibitors (SNRIs) for fibromyalgia syndrome (Walitt 2015);Serotonin and noradrenaline reuptake inhibitors (SNRIs) for fibromyalgia syndrome (Häuser 2013 a)Tricyclic agents for fibromyalgia syndrome. …”
Section: Notesmentioning
confidence: 99%
“…Case reports and case series suggest that certain secondgeneration agents, notably citalopram, venlafaxine, and bupropion, as well as selected antipsychotic medications, might be more hazardous in overdose (11)(12)(13)(14)(15)(16)(17)(18)(19). However, few reports have systematically compared the morbidity and mortality of the array of agents used to treat depression.…”
mentioning
confidence: 99%
“…4,5) A number of reports have indicated that the medication is generally well tolerated and has significant efficacy, although a few reports have suggested inconclusive data. [6][7][8] These evaluations have been mainly focused on the socio-economical impact as well as on the induction of co-lateral health damage; however, very limited reports have been published regarding the effect of duloxetine on the genetic material, which may be a significant biomarker for future disease development. In the genotoxicity area of research we only found a report that measured genotoxicity in mice with negative results in blood and brain cells.…”
mentioning
confidence: 99%